SANKSI ADAT TERHADAP WARGA YANG MELAKUKAN PERKAWINAN SUMBANG PADA MASYARAKAT DAYAK PESAGUAN HULU - NIM. A1011201131, FLOURENCE WYNNIE BUDIONO (Fakultas Hukum Universitas Tanjungpura, 2024)
AbstractIn the Dayak Pesaguan Hulu indigenous community, there are customary prohibitions on incestuous marriages that have been passed down through generations. Incestuous marriage is prohibited due to the belief that it can invite misfortune and calamity for both the descendants and the couple involved. The community holds negative views toward such marriages.The research problem formulated is